Tinjauan Kompilasi Hukum Ekonomi Syariah (KHES) Terhadap Jual Beli Getah Karet (Studi di Desa Petai Kayu Kecamatan Semidang Alas, Kabupaten Seluma, Bengkulu) - Arista Khairunnisa (Journal of Islamic Business Law, 2018)
The objective of the research is to describe how the contemplation of Sharia Law Compilation Economic (KHES) about purchase and sale of rubber latex in Petai Kayu village which had weight cutting unilateral. The type of the research is empirical juridical with empirical juridical and conceptual approach which is correlate the fact according to Sharia Law Compilation Economic. Collecting data method through interview to the farmer and purchaser of rubber latex. Data analyzed by editing and verification data from interview, classification to the information which had collected before. The verification doing to the result of interview which collected by tape recorder and then analyze the data with the regulation in Sharia Law Compilation Economic and then conclusion from the data which analyzed. Research finding in this research are (1) there are wood cutting unilateral by middleman in the purchase and sale of rubber latex because high level of liquid content in the rubber latex. wood cutting up to10%from the weight of rubber latex when its ponder able or 1kg up to 2kg even more. Farmers indisposed with the unilateral cutting. (2) The result of analyzing purchase and sale of rubber latex with weight cutting in Petai Kayu Village according to Sharia Law Compilation Economic still found an insatiable prerequirement so it can be regarded fasid.